2008
DOI: 10.1111/j.1538-7836.2008.03121.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of different IgG anticardiolipin antibody cut‐off values on antiphospholipid syndrome classification

Abstract: Summary. Background: While medium to high titers of anticardiolipin (aCL) antibodies, defined as >40 GPL units or >99th percentile, is a laboratory criteria for the ÔdefiniteÕ diagnosis of antiphospholipid syndrome (APS), agreement between the two cut-offs has not been validated. Objective: To validate the current aCL laboratory criterion by verifying the effect of the two cut-offs on APS classification. Patients/ methods: Ninety aCL positive APS patients were selected on the basis of their GPL values above th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
75
1
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(84 citation statements)
references
References 22 publications
5
75
1
2
Order By: Relevance
“…In two recent studies Ruffatti et al and Devreese et al show that the 99th percentile of controls is not sufficient to define an optimal cut-off. 8,9 Most patients with clinical manifestations of APS have higher aCL values. 8,9 Moreover the 99th percentile of normal controls and 40 GPL units are not equivalent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In two recent studies Ruffatti et al and Devreese et al show that the 99th percentile of controls is not sufficient to define an optimal cut-off. 8,9 Most patients with clinical manifestations of APS have higher aCL values. 8,9 Moreover the 99th percentile of normal controls and 40 GPL units are not equivalent.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 Most patients with clinical manifestations of APS have higher aCL values. 8,9 Moreover the 99th percentile of normal controls and 40 GPL units are not equivalent. 8,9 To identify high positivity it is possible to use a threshold defined by the 99th percentile of disease controls.…”
Section: Discussionmentioning
confidence: 99%
“…The difference in the results may depend on the differences in the selected cohorts as the risk of pregnancy loss is low in LA-negative patients [89]. In addition, most patients diagnosed with primary obstetric APS are only aCL positive [90]. Until evidence from clinical trials enroling patients with a uniform aPL profile (confirmed in a reference laboratory) becomes available, obstetric (alone) complications in LA-negative patients should be treated with a prophylactic dose of LMWH and lowdose aspirin.…”
Section: Treatment Of Pregnant Patients With Apsmentioning
confidence: 99%
“…The Journal of on May 11, 2018 -Published by www.jrheum.org Downloaded from patients with thrombotic APS (16.9%) and those with both conditions (16.7%) 13 . Consistently, pregnancy outcomes in untreated patients with low aPL levels and APS-like obstetrical events are similar to women with classical APS; moreover, conventional treatment with LDASA with or without LMWH improved pregnancy outcomes to an extent comparable to otherwise healthy women with REM 14 .…”
Section: Rheumatologymentioning
confidence: 99%